Kajian Historis terhadap Perkembangan Resolusi Konflik Etnis dan Agama di Bosnia-Herzegovina - Fikri Surya Pratama (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Politically and geographically, Bosnia is often a victim of the Western political divisive propaganda and extremist Islamic movements. This has left Bosnia and Herzegovina embroiled in ethnic and religious conflicts between Bosnians, Serbs and Croats for decades. This journal article explores the history of ethno-religious conflict in Bosnia, and how the government has created a peaceful, multi-ethnic and religious European Muslim nation amid radical siege of